DIMENSION AND ANALYTICS IN SLOW GROYH CRACK ON MATERIAL VISCO-ELASTICITY - ekateshwara1, Pro. Himadri V (International Journal of Multidisciplinary Research and Studies, 2021)
Apparatus for studying slow crack growth during a polymer is described. A theoretical analysis is made public which relates the speed of growth to the stress intensity factor and material properties and demonstrates how the visco-elastic behavior of the polymer is chargeable for slow crack growth. The analysis predicts a intensity of stress intensity below which crack growth under static load mustn’t occur. Experimental data on slow crack growth in two grades of PVC are obtained for comparison with theoretical predictions. Difficulties experienced with the gathering of stable growth data on these materials are associated with the occurrence of transient growth. The speculation is observed to explain slow growth in an exceedingly small range of stress intensity close to the edge only. At higher levels, experimental growth rates for both PVC grades are much under theoretical values and also the range of stress intensity giving stable growth is larger than that predicted. A modification to the theoretical analysis is taken into account which attempts to model more accurately the behavior of the plastic zone material, and preliminary calculations have indicated that this produces a much better description of experimental data.